2018
DOI: 10.26417/ejis.v4i2.p45-51
|View full text |Cite
|
Sign up to set email alerts
|

Genocide Denial: A Form of Evil or a Type of Epistemic Injustice?

Abstract: In this paper, I bring together the philosophical scholarship on evil and the literature on “epistemic injustice” in order to assess effective vocabulary to understand the phenomenon of genocide denial. I use the term “denial” to denote the discursive political tactic that makes the evil of genocide invisible. Adi Ophir’s discussion of “two orders of evil” allows us to consider genocide denial as a form of evil. For what Ophir identifies as a second-order evil, another stream of scholarship suggests the term “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Denials of historical injustice, either state-or individual-led, often involve epistemic injustices. Oranli (2018) shows, for instance, that Armenian genocide denials involve testimonial injustice, hermeneutical injustice, and unjust distribution of epistemic resources. For instance, genocide denialists attribute deflated credibility to the survivors (and their kin), thereby silencing the survivors and preventing knowledge about the injustice (Oranli 2018, 50).…”
Section: Denial and Epistemic Injusticementioning
confidence: 99%
“…Denials of historical injustice, either state-or individual-led, often involve epistemic injustices. Oranli (2018) shows, for instance, that Armenian genocide denials involve testimonial injustice, hermeneutical injustice, and unjust distribution of epistemic resources. For instance, genocide denialists attribute deflated credibility to the survivors (and their kin), thereby silencing the survivors and preventing knowledge about the injustice (Oranli 2018, 50).…”
Section: Denial and Epistemic Injusticementioning
confidence: 99%
“…These connections are worth further exploration. They include connections to discussions in epistemic injustice (Pantazatos, 2017), heritage (Matthes, 2016(Matthes, , 2018a(Matthes, , 2023, evaluating the past and the relativism of distance (Archer & Matheson, 2024;Moody-Adams, 2002;Williams, 1985), cultural genocide (Altanian, 2021a(Altanian, , 2021bOranli, 2018;Oranlı, 2021), or political representation (Dovi, 2018), just to name a few. Similarly, it also may benefit from interacting more with other disciplines such as cultural studies, Black studies, education studies, architecture, geography, or urban studies.…”
Section: Gaps and Future Directionsmentioning
confidence: 99%
“…Similarly, Oranli (2020) argues that the Turkish denial of the Armenian genocide constitutes and produces pervasive and systematic epistemic harms. In an earlier paper, Oranli (2018) demonstrated that the denial of the Armenian genocide involves several forms of epistemic injustice such as testimonial injustice, hermeneutical injustice and the unjust distribution of epistemic resources. In a more recent paper, Oranlı (2020) draws on the work of Fricker (2007), Medina (2013) and Mills (2017) to demonstrate the interrelatedness of individuals who perpetrate genocide denialism, the ideology behind denialism and the institutions supporting genocide denialism.…”
Section: Denial Of Past Wrongdoing As Epistemic Injusticementioning
confidence: 99%